Chalcidoid parasitoids of Micrurapteryx sophorivora [Lepidoptera: Gracillariidae] in Kuluncak, Turkey / Parasitoïdes chalcidoïdes de Micrurapteryx sophorivora [Lepidoptera : Gracillariidae] de la région de Kuluncak en Turquie - Gençer, Lütfiye; Seven, Selma (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2005)
This study deals with the parasitoids of Micrurapteryx sophorivora. Parasitoids of M. sophorivora were investigated on Robinia pseudoacacia in 2004 in the Kuluncak district, Turkey. Seven parasitoid species, Baryscapus nigroviolaceus, Cirrospilus pictus, Necremnus croton, Neochrysocharis arvensis, Neochrysocharis formosa, Pnigalio sp. and Pteromalus sp., were reared. Necremnus croton was found to be the most common parasitoid. All the parasitoids reared were recorded for the first time from Micrurapteryx sophorivora.